Implementation of an EEG-based game using a brain computer interface for attention training - Yeo, Heng Gene (Nanyang Technological University, 2023)
The Centre for Brain-Computing Research (CBCR) in Nanyang Technological University (NTU) has developed ways where we can make use of Brain-Computer Interfaces (BCI) to read the electrical activities of the brain, allowing us to determine whether a person is giving attention or focusing on a task. With the existence of such technology, this project seeks to develop an EEG-based game that can make use of BCI for attention training. This report first introduces us to the use to BCI to obtain neurofeedback from the player, as well as looking into effective methods that can be used to train attention. It will then go into details how the attention training game, Last Hope, is developed and how it can be played. Lastly, it will investigate the effectiveness of Last Hope in training the attention of its players and what can be improve on it.